A Comprehensive Review of Advances in Radiation Science and Applications - Alyami, Saleh Hadi Hussein; Alyami, Hamad Ali Mahdi; Almehthel, Yaqoub Awaid M; Alyami, Ali Saleh H; mutarid, Ali Fohid Mohamad Al; shreeh, Naif Hamad Al; algshanin, Naif ghanem saleh; alrakah, Fayez mahdi; Alyami, Hassan Ali; algshanin, Abdullah ghanem saleh (Journal of Ecohumanism, 2024)
There have been many improvements in the field of radiation science in the last few decades, fueled mainly by technology and physical knowledge of the event. This paper gives an overview of the recent advancements in radiation science, Whi ch includes some compound semiconductor materials like gallium arsenide (GaAs), Aluminum Nitride (AlN), and Indium Phosphide (InP). They are widely becoming influential actors in the construction of radiation sensors, detectors, and other uses in healthcare and space travel, among many other fields. This review not only summarises the latest research in the area but also discusses the methodologies used in radiation interaction research, important applications, and possible future trends.